Effectiveness and Economic Feasibility of Gas Turbine Inlet-Air Cooling by Air Washing in the Hot and Dry Climate of Sudan (University of Khartoum Engineering Journal, 2022)
This paper studies the effectiveness and economic feasibility of cooling the gas-turbine's inlet-air by airwashing (AW) compared to wetted-media evaporative cooling (WMEC) in the hot and dry climatic conditions ofSudan. Measurements were made on an experimental test rig to determine the cooling effect of the WMEV andthat of AW with water at ambient temperature and with chilled water. Taken at two seasons of the year withdifferent ambient temperature and humidity levels, the experimental results were used to estimate the revenues thatthe systems can generate as a result of increased megawatts and reduced heat rate of a typical gas turbine model(GE PG6581B). The calculations indicate that the WMEC system can increase the gas turbine output by 12% andreduce its heat rate by 1.6%. Using un-chilled water, the AW system can increase the output by 16.7% and reducethe heat rate by 2.2%, while with chilled water it can increase the power by 23.3% and reduce the heat rate by3.1%. Based on these estimates, the WMEC system requires a payback period of 8 months if run for 4 hours daily,which reduces to 4 months if used for 8 hours. AW with un-chilled water has a payback period of about 8 months,but the pay-back period for the chilled-water AW system is about 5 years.